You have

x + x + 3 - 1*6 + 2 - 1 = 35 + 35 + (-1) + 4

2x + 3 - 6 + 2 - 1 = 70 - 1 + 4

2x - 3 + 2 - 1 = 69 + 4

2x - 1 - 1 = 73

2x - 2 = 73

2x = 75

x = 75/2

75 + 3 - 6 + 2 - 1 = 70 - 1 + 4 (perform the first level of simplification)

80 - 7 = 74 - 1 (combine positive numbers, combine negative numbers)

73 = 73 (evaluate. Our answer checks.)

x + x + 3 - 1*6 + 2 - 1 = 35 + 35 + (-1) + 4

2x + 3 - 6 + 2 - 1 = 70 - 1 + 4

2x - 3 + 2 - 1 = 69 + 4

2x - 1 - 1 = 73

2x - 2 = 73

2x = 75

x = 75/2

**x = 37.5**__Check__37.5 + 37.5 + 3 - 1*6 + 2 - 1 = 35 + 35 - 1 + 4 (substitute the number 37.5 for x)75 + 3 - 6 + 2 - 1 = 70 - 1 + 4 (perform the first level of simplification)

80 - 7 = 74 - 1 (combine positive numbers, combine negative numbers)

73 = 73 (evaluate. Our answer checks.)